The different natures of the same object - Borges, Paulo César Balardim (2024)
The text presents Móin -Móin - Journal of Studies in the Arts of Puppetry 29th edition, with has the theme “Object Theater, Memory and History” and their context of composition, showing the main questions that induces the authors and presents a synthesis of the published articles.